Peranan Perdagangan Internasional Sebagai Salah Satu Sumber Pertumbuhan Ekonomi Indonesia - Khaidar Rahmaini Jamila; Vera Maytara (CV. Ulil Albab Corp, 2023)
This study aims to determine the role of international trade as a source of economic growth in Indonesia. The method used in this research is qualitative with descriptive type. The data obtained is sourced from several secondary information obtained through websites, articles, journals that are in line with the research theme. International trade has a significant influence on economic growth in a country, especially in developing countries, for example in Indonesia. Export and import activities such as sales of goods and services or capital are one of the factors that influence economic growth in a country. The results of the study say that exports carried out by the Indonesian state through a wealth of quality spices and petroleum are one of the driving factors in economic growth in the country of Indonesia. However, people in Indonesia have a high desire to consume goods produced by foreign countries and often Indonesian people follow the consumption pattern of foreign countries. This makes the income generated by the state due to exports which should be used as savings to decrease because the level of consumption or imports of the people continues to increase.